El ensayo y las prácticas editoriales - Hutnik, Elizabeth Tamara (2012)
En este trabajo analizaremos los llamados "libros de ensayo" desde una perspectiva editorial. Para ello, haremos una revisión de la categoría de ensayo atendiendo a su forma, los procedimientos que emplea, los temas que aborda, su relación con el sujeto autoral, su vínculo con el conocimiento y el discurso científico, y su lugar dentro del campo editorial. En última instancia, y a partir de la teoría económica de los commodities, exploraremos las características del ensayo como bien cultural y como bien material.
In this paper we will analyse the so-called "essay's books" from the publishing perspective. In that way, we will study the very notion of "essay" with regards to: a) form; b) literary procedures; c) topics; d) the author / subjectivity; e) the relationship with knowledge; f) the link with scientific discourse; g) its place in the publishing field. Last but not least, we will explore some essay's characteristics from the point of view of the Economic Theory of Commodities. We will analyse the essay attending to its double construction: as a cultural and as a material product.
Keywords: Ensayo; Práctica editorial; Mercado; Commodity; Estudios Generales del Lenguaje; Lengua y Literatura